ChemInform Abstract: Ethynylation of 2‐(Furan‐2‐yl)‐ and 2‐(thiophen‐2‐yl)pyrroles with Acylbromoacetylenes in the Al2O3 Medium: Relative Reactivity of Heterocycles. Issue 17 (April 2015) - Sobenina, Lyubov' N.; Petrova, Ol'ga V.; Tomilin, Denis N.; Gotsko, Maxim D.; Ushakov, Igor' A.; Klyba, Lyudmila V.; Mikhaleva, Al'bina I.; Trofimov, Boris A.
Abstract Simple grinding of the title substrates with Al2O3 results in highly selective ethynylation of the pyrrole rings.